Wheat and Grain Sorghum Sequencing for Three Crops in Four-Year Rotations - Lucas A. Haag; Dewayne Bond; Amanda Burnett; Jeffrey Slattery; Alan Schlegel (Kansas Agricultural Experiment Station Research Reports, 2023)
In 1996, an effort began to quantify soil water storage, crop water use, and crop productivity on dryland systems in western Kansas. Research on 4-year crop rotations with wheat and grain sorghum was initiated at the Southwest Research-Extension Center near Tribune, KS. Rotations were wheatwheat- sorghum-fallow (WWSF), wheat-sorghum-sorghum-fallow (WSSF), and continuous wheat (WW). Soil water at wheat planting averaged about 9.1 in. following sorghum, which is about 3.8 in. more than the average for the second wheat crop in a WWSF rotation. Soil water at sorghum planting was only about 1.5 in. less for the second sorghum crop compared with sorghum following wheat. Sorghum grain yield in 2022 was near average for first crop sorghum after wheat, above average for recrop sorghum, and below average for sorghum after recrop wheat. Wheat yields in 2022 were near zero due to hail. Wheat yields, when averaged across years, have been 2 bu/a greater following two sorghum crops than following one sorghum crop. Average sorghum yields were the same following one or two wheat crops. Yield of the second sorghum crop in a WSSF rotation averages 66% of the yield of the first sorghum crop.
Keywords: No-till; continuous cropping; wheat; grain sorghum